Dipeptidyl peptidase 4 levels as a novel potential early marker in the identification of complicated appendicitis - Saucedo Zamora, Brandol D.; García Chávez, Luis E.; Torres Montelongo, Ivan A.; Araiza Martínez, Carlos A.; Valencia Sánchez, Liliana D.; Medina Moreno, Ursula F. (International Journal of Research in Medical Sciences, 2025)
Background: Appendicitis represents one of the most prevalent indications for emergency department care due to abdominal pain. Complications risk depends on how soon are diagnosed. Test like c-reactive protein (CRP) and neutrophil-lymphocyte index (NLI) can assist in diagnose complications, but they are not always precise. Dipeptidyl peptidase 4 (DPP4) has been employed as a new marker in other inflammatory pathologies; thus, exist the potential for its use in pathologies such as appendicitis. Evaluate the utility of serum levels of DPP4, CRP and INL in identify and differentiate complications in patients with histopathologically confirmed appendicitis. Methods: A cohort study with diagnostic test analysis included patients aged 18-80 years with suspected appendicitis undergoing surgery. They had given informed consent to participate. A minimum of 30 subjects per group was considered. Complicated and uncomplicated appendicitis was diagnosed by histological examination of tissue samples. Sensitivity and specificity of DPP4, CRP levels and NL index in diagnosis of complicated appendicitis were determined. Results: We observed higher levels of DPP4 (7820 vs 5250 pg/dl,) and CRP (4 vs 10 mg/dl) in complicated appendicitis group. These levels were statistically significant (p=0.03; p=0.02, respectively). Sensitivity for DPP4 was 50% versus 64% for CRP and 57% for INL. Specificity of DPP4 was 83% compared to 70% for CRP and 76% for INL. Conclusions: Compared to CRP and INL, DPP4 levels showed lower sensitivity but higher diagnostic specificity in our population. In acute appendicitis, DPP4 levels could be an early indicator in addition to imaging and clinical assessment of patients.